Crystal structure of bis(μ2-aqua)diaquasodium 4-azidobenzenesulfonate monohydrate, Na(H2O)4[N3C6H4SO3] · H2O - Biesemeier Frank; Harms Klaus; Müller Ulrich (Zeitschrift für Kristallographie - New Crystal Structures, 2004)
C6H14N3NaO8S, monoclinic, P121/c1 (no. 14), a = 7.018(1) Å, b = 27.193(5) Å, c = 7.089(1) Å, β = 92.01(2)°, V = 1352.0 Å3, Z = 4, Rgt(F) = 0.071, wRref(F2) = 0.160, T = 193 K.